Effect of design variation on tpms geometries manufactured by additive manufacturing - Chixaro, Davi Salvini; Drozda, Fabiano Oscar; Silva, RicardoRicardo Júnior De Oliveira; Lajarin, Sérgio Fernando (Brazilian Journal of Production Engineering, 2024)
Additive Manufacturing has become a useful process for producing highly customizable and complex products. DLP technology is employed across fields such as medicine, dentistry, footwear, and safety equipment due to its high resolution in detailing produced parts. Triply Periodic Minimal Surface (TPMS) structures have been studied since the 19th century as curved proposals devoid of sharp corners, thereby hindering crack propagation under mechanical stress. Due to their complexity, their manufacture was previously impossible before the advent of additive manufacturing technologies. Analyzing studies on TPMS structures reveals a lack of defined design parameters and their influence on compression mechanical tests, as well as comparisons between structures. This study aimed to evaluate the most studied TPMS structures gyroid, diamond, and Schwarz P and their design parameters such as cell size and wall thickness, to analyze their behaviors under compression tests. Results indicated that cell size did not show statistical significance, whereas geometry and wall thickness exhibited a strong relationship with calculated elasticity modulus values.
Keywords: Additive Manufacturing; Digital Light Processing; Triply Periodic Minimal Surfaces; TPMS; DLP